The Development and Implementation of a Novel Electronic Consult (E-Consult) System by a Laboratory Medicine Service: Experience From the First 2 Years of Use. (21st September 2018) - Stendahl, Kristin; Siddon, Alexa; Peaper, David; Hauser, Ronald; Campbell, Sheldon; Tormey, Christopher
Abstract: Introduction: A novel electronic consult (e-consult) system for the Pathology and Laboratory Medicine Service (PLMS) at a high-complexity Veterans Administration Healthcare facility was implemented in 2015. The e-consult process involves resident review followed by attending review and co-signature. Before this, consults were made through direct provider communication without documentation in the medical record. We evaluated trends in utilization of the lab e-consult system by providers at our facility over the first 2 years since its inception. Methods: E-consults completed by PLMS from 2015 to 2017 were reviewed to record the type of consult, date, requesting department, and patient location. Results: E-consults totaled 351 over the study period. The volume varied by laboratory subsection: hematology (n = 215/351, 61.2%), clinical chemistry (109/351, 31.1%), blood bank (19/351, 5.4%), and microbiology (8/351, 2.3%). The hematology consults were for peripheral blood smear review (215/215, 100%), while the chemistry consults were for toxicology/drugs of abuse (81/109, 74%), test utilization (17/109, 16%), or nontoxicology (11/109, 10%). Nine services placed consults, with the majority from three services: primary care (279/351, 80%), hematology/oncology (39/351, 11%), and psychiatry (27/351, 8%). Most e-consults were requested on outpatients (309/351, 88%). Since e-consult implementation, the mean number of consults per month increased from 8.6 in 2015 to 18.1 in 2017, peaking in the last quarter of our analysis in 2017 with a mean of 25.3 consults per month. Conclusion: Our novel e-consult system was popular among a broad scope of ordering providers and improved accessibility to, and documentation of, answers to complex laboratory questions. In addition, it raised the hospital-wide visibility of our section. Future goals include development of outcomes-based measures to more fully assess the clinical impact of this consult mechanism.